Exploring EFL Students Cognition and Practices in Applying English Speaking Through the Use of AI (Artificial Intelligence) - Namira Fasya Khailifa; Pirman Ginting (Institut Agama Islam Negeri Palopo, 2024)
AI (Artificial intelligence) is a design of technology that has been significantly useful for human in all aspects, particularly in education. In education systems, AI has become essential in providing the needs of students especially in english speaking skills. The development of AI (Artificial Intelligence) technology has enhanced the cognition and practices of EFL students in applying english speaking skills. This current study attempts to unleash the extent to which the speaking skills obtained by the EFL students with the use of AI. 15 EFL students in SMA N 10 Medan participated in this study. The research design employed mix method included qualitative and quantitative method. Pre-test and post-test was employed as an instrument of collecting data. The technique of analyzing data involved descriptive statistics and paired sample t-test were conducted to achieve the quantitative analysis. Meanwhile, thematic analysis was conducted to acquire the qualitative analysis. The result revealed that the majority of participants believed their cognition and practice in english speaking skills have improved with the assistance of AI. The findings also revealed that AI considered as fun, easy and practical alternative to practice english speaking proficiency. Therefore, it is suggested to all students could access AI as a tool that supports continuity of learning.